Effects of Elevated CO2 on Leaf Senescence, Leaf Nitrogen Resorption, and Late-Season Photosynthesis in Tilia americana L. - Li, Li; Wang, Xiaoke; Manning, William J. (Frontiers in Plant Science, 2019)
We investigated the effects of elevated CO2 concentrations ([CO2]) on autumnal leaf fallen, late-season photosynthesis and leaf N resorption efficiency by exposing Tilia americana L. to three CO2 levels (800 ppm-A8, 600 ppm-A6 and ambient air-A4) in 9 continuous stirred tank reactors (CSTRs). All leaves were subdivided into the first (Z1), second (Z2) and third bud break (Z3) leaves. Whole plant photosynthesis (PNsat) was determined by summing the products of PNsat and total leaf area in Z1, Z2 and Z3, respectively. The results indicated that: 1). The timing of leaf senescence in A8 treatments was 21 days in advance, while the senescence duration sustained 20 days longer than ambient treatment. 2) Elevated [CO2] significantly induced the early formation of overwintering buds, with the number increased by 42% and 29% in A8 and A6 treatments, respectively. 3) Z3 leaf photosynthesis increases consistently until the end of the growing season but Z2 leaves and whole plant showed acclimation when senescence happened. 4) Autumnal N resorption efficiency in A8 and A6 leaves were 25.5% and 22.7% higher than A4, respectively. In conclusion, autumnal senescence of Tilia americana L. was accelerated while the leaf fallen duration was extended by elevated [CO2]. which leads to. The change in leaf phenology makes a higher N resorption efficiency, earlier and more winter buds formation possible. Meanwhile, a different response of PNsat within different bud break leaves lead to the disparity between instantaneous measurements of leaf photosynthesis and whole plant photosynthesis in end season.